Pengaruh Penggunaan Bahasa Indonesia yang Inklusif Terhadap Keberagaman di Lingkungan Mahasiswa Pendidikan Manajemen Perkantoran - Sayyidah, Haya Auliya Kultsum; Humaira, Hanifa Aurelia; Permata, Ilmas; Rusmayanti, Intan Citra; Agiesta, Ismi Alya Dwi; Rizkyanfi, Mochamad Whilky (Indo-MathEdu Intellectuals Journal, 2025)
Cultural, ethnic, and linguistic diversity in Indonesia presents challenges in building inclusive communication within higher education, particularly in the Office Management Education study program. This study aims to examine the impact of using inclusive Indonesian language on creating a harmonious academic atmosphere, increasing tolerance, fostering cooperation, and enhancing social engagement among students from various cultural backgrounds. The research employs a qualitative method through semi-structured interviews with students from diverse regional and cultural backgrounds. The data from the interviews was then analyzed using thematic analysis, which is the process of identifying, grouping, and interpreting patterns of meaning that emerge in the participants' narratives. The findings indicate that the use of inclusive Indonesian language strengthens mutual respect, reduces communication barriers, and promotes social integration on campus. However, challenges remain, such as a lack of awareness in choosing neutral words and the influence of foreign terms in academic communication. In conclusion, mastering inclusive Indonesian is an essential competency for developing adaptive and ethical professional character in cross-cultural communication within the multicultural environment of office management education